Presence of fetal microchimerisms in the heart and effect on cardiac repair - Llorente, Vicente; López-Olañeta, Marina; Blázquez-López, Elena; Vázquez-Ogando, Elena; Martínez-García, Magdalena; Vaquero, Javier; Carmona, Susana; Desco, Manuel; Lara-Pezzi, Enrique; Gómez-Gaviro, María Victoria (Frontiers in Cell and Developmental Biology, 2024)
Multiple complex biological processes take place during pregnancy, including the migration of fetal cells to maternal circulation and their subsequent engraftment in maternal tissues, where they form microchimerisms. Fetal microchimerisms have been identified in several tissues; nevertheless, their functional role remains largely unknown. Different reports suggest these cells contribute to tissue repair and modulate the immune response, but they have also been associated with pre-eclampsia and tumor formation. In the maternal heart, cells of fetal origin can contribute to different cell lineages after myocardial infarction. However, the functional role of these cells and their effect on cardiac function and repair are unknown. In this work, we found that microchimerisms of fetal origin are present in the maternal circulation and graft in the heart. To determine their functional role, WT female mice were crossed with male mice expressing the diphtheria toxin (DT) receptor. Mothers were treated with DT to eliminate microchimerisms and the response to myocardial infarction was investigated. We found that removal of microchimerisms improved cardiac contraction in postpartum and post-infarction model females compared to untreated mice, where DT administration had no significant effects. These results suggest that microchimerisms play a detrimental role in the mother following myocardial infarction.